Genes encoding proteoglycans are associated with the risk of anterior cruciate ligament ruptures. Issue 22 (19th February 2014) - Mannion, Sasha; Mtintsilana, Asanda; Posthumus, Michael; van der Merwe, Willem; Hobbs, Hayden; Collins, Malcolm; September, Alison V
Abstract : Background: Genetic variants within genes involved in fibrillogenesis have previously been implicated in anterior cruciate ligament (ACL) injury susceptibility. Proteoglycans also have important functions in fibrillogenesis and maintaining the structural integrity of ligaments. Genes encoding proteoglycans are plausible candidates to be investigated for associations with ACL injury susceptibility; polymorphisms within genes encoding the proteoglycans aggrecan ( ACAN ), biglycan ( BGN ), decorin ( DCN ), fibromodulin ( FMOD ) and lumican ( LUM ) were examined. Methods: A case–control genetic association study was conducted. 227 participants with surgically diagnosed ACL ruptures (ACL group) and 234 controls without any history of ACL injury were genotyped for 10 polymorphisms in 5 proteoglycan genes. Inferred haplotypes were constructed for specific regions. Results: The G allele of ACAN rs1516797 was significantly under-represented in the controls (p=0.024; OR=0.72; 95% CI 0.55 to 0.96) compared with the ACL group. For DCN rs516115, the GG genotype was significantly over-represented in female controls (p=0.015; OR=9.231; 95%CI 1.16 to 73.01) compared with the ACL group and the AA genotype was significantly under-represented in controls (p=0.013; OR=0.33; 95% CI 0.14 to 0.78) compared with the female non-contact ACL injury subgroup. Haplotype analyses implicated regions overlapping ACAN (rs2351491 C>T-rs1042631 T>C-rs1516797 T>G), BGN (rs1126499 C>T-rs1042103 G>A) and LUM - DCN (rs2268578 T>C-rs13312816 A>T-rs516115 A>G) in ACL injury susceptibility. Conclusions: These independent associations and haplotype analyses suggest that regions within ACAN, BGN, DCN and a region spanning LUM – DCN are associated with ACL injury susceptibility. Taking into account the functions of these genes, it is reasonable to propose that genetic sequence variability within the genes encoding proteoglycans may potentially modulate the ligament fibril properties.